Analysis of Conflicts in an IT Company: Evidence from Romania - Dana Corina DESELNICU; Alexandra IOANID; Mircea Constantin OPRIS (Communications of International Proceedings, 2021)
In the modern organizations conflict is a significant and frequent phenomenon. The purpose of the present study was to analyze the conflicts within a department of the Romanian IT company ALPHACERT, including their identification, evaluation and resolution. A self-administered online questionnaire was applied to 30 employees from the department. The results indicated that the main category of work conflicts was the hierarchical interpersonal one between managers and subordinates. As causes generating the conflicts, the respondents indicated poor communication, the inadequate reward system and competition at work. The paper advances several mitigation methods for the conflict situations to be efficiently resolved, the employees’ satisfaction raised, the staff turnover reduced, and the interpersonal and intergroup relations within the company harmonized.
Keywords: Work conflict; conflict resolution; conflict management.